Analyzing the long-term effects of beta-blocker therapy on cardiac function and mortality rates in post-myocardial infarction patients: A Systematic Review - ATEF EID MADKOUR ELSAYED; Mohamed Amin Abdelsalam; Asmaa Husain Mohammad Alhibshi; Rawan Haytham Raffah; Rola Safar Abdullah Alghamdi; Hamoud Saleh Almutairi; Moaad Abou Safrah; Hadia Bremia Osman Bader; JumanaEbrahim Abdulla Alwatani; Abdulrasool Yaser Abdulrasool Ebrahim; et al. (The Bioscan, 2025)
Background: Beta-blockers are foundational in the management of myocardial infarction (MI). However, their long-term utility in patients with preserved left ventricular ejection fraction (LVEF ≥50%) remains uncertain in the modern reperfusion era. Objective: To systematically review and synthesize contemporary evidence evaluating the impact of long-term beta-blocker therapy on mortality, reinfarction, and hemodynamic outcomes in post-MI patients with preserved ejection fraction. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Databases including PubMed, Scopus, Embase, Web of Science, and Google Scholar were searched for English-language peer-reviewed studies published between 2010 and 2025. Eligible studies included randomized controlled trials, cohort studies, meta-analyses, and systematic reviews evaluating long-term beta-blocker therapy in post-MI patients with LVEF ≥50%. Results: Eighteen studies met the inclusion criteria. The majority found no significant mortality benefit associated with long-term beta-blockers in patients without heart failure. Subgroup analyses showed potential benefits in individuals with elevated heart rate or hypertension. Several studies emphasized the short-term utility of beta-blockers, particularly within the first year post-MI. Conclusion: In the era of modern revascularization and medical therapy, the routine continuation of beta-blockers in MI survivors with preserved EF may not confer long-term survival benefits. A tailored, patient-centered approach should guide therapy decisions.